(untitled) (Journal of the Bangladesh Agricultural University, 2025)
The study was aimed to observe the feasibility and economic viability of the floating duck house (FDH) and evaluate the growth of Jinding ducks reared on the floating duck house. The FDH house was constructed with locally available materials. The length and width of the FDH were 18 feet and 14 feet respectively. A total of 150-day-old ducklings were collected and reared up to 12 weeks of age to observe the growth performance of Jinding ducks. After completion of brooding of ducklings in a brooder house, the ducks were then transferred and reared on the FDH. The ducklings were fed a starter diet up to 4 weeks of age and self-formulated feed up to 12 weeks of age. During the experimental period, feed intake, live body weight, body weight gain, feed conversion ratio (FCR), survivability and benefit-cost ratio were recorded and calculated. The result showed that the Factor of Safety (Fs) of the FDH was 4.04 that is higher than recommended minimum suggested value (2.5), asserting the ability of the FDH to float with this existing load. The average final body weight, body weight gain, feed intake, and FCR were determined to be 1647.25 g/bird, 1605.35 g/bird, 5099.42 g/bird, and 3.18 respectively after calculating all growth data. About 96.67% of ducks were survived during this experimental period, and the net profit was Tk. 42.51/-.per kg live birds. Thus, it can be inferred that raising ducks in floating duck houses specially designed for low-lying areas such as haor would be a suitable option to ensure the profitability and economic viability of the duck farming enterprise. J Bangladesh Agril Univ 23(2): 193-200, 2025